2020
DOI: 10.46238/jobda.823955
|View full text |Cite
|
Sign up to set email alerts
|

How Does Covid-19 Pandemic Effect Online Shopping in E-Commerce?

Abstract: Anbar 2001). Online shopping is cheaper in some parts of the retail sector, access to website with fast access, finding products, price comparisons, 24/7 shopping opportunity, gift and discount days make e-commerce attractive (Uğur 2016). In addition to its attractive features, some negativities are experienced and these situations cause customers to hesitate to shop online and avoid using it (Demirel 2010).In this study, examining the factors of electronic commerce affecting the use of online shopping website… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Some studies that have been developed focusing on the pandemic period confirm the same and report that purchasing decisions were positively affected by trust, which in turn presents a positive relationship with satisfaction when shopping online ([Parlakkiliã et al, 2020], [Attar et al, 2020]). However, some authors go so far as to say that the shopper had no alternatives in a lockdown context and trust could be put aside but the lack of confidence could motivate a return to traditional commerce when shoppers can do so (Bonisoli and Castillo Leyva [2022]).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Some studies that have been developed focusing on the pandemic period confirm the same and report that purchasing decisions were positively affected by trust, which in turn presents a positive relationship with satisfaction when shopping online ([Parlakkiliã et al, 2020], [Attar et al, 2020]). However, some authors go so far as to say that the shopper had no alternatives in a lockdown context and trust could be put aside but the lack of confidence could motivate a return to traditional commerce when shoppers can do so (Bonisoli and Castillo Leyva [2022]).…”
Section: Introductionmentioning
confidence: 70%
“…Online shopping has grown exponentially over the last decade and is regarded as a way for businesses to reach new customers ([Habib et al, 2022]; [ITA Publishing, 2024]). Particularly, during the period of the COVID 19 pandemic, significant growth was reported by several studies ([ITA Publishing, 2024], [Al-Azzawi et al, 2021], [Parlakkiliã et al, 2020], [McKibbin and Fernando, 2021]). E-commerce websites play an essential part in online shopping because of their ability to reach and attract customers online, increasing user satisfaction and, as a result, attracting the attention of marketing practitioners, society, and academics.…”
Section: Introductionmentioning
confidence: 99%
“…Their study showed that 52 percent of shoppers avoided going to physical stores and congested places, and furthermore, 36 percent said they would not go shopping until they had obtained the coronavirus vaccine. And (Parlakkılıç, 2020) noted how consumer payment behavior changed as a result of the pandemic, with consumers and producers switching to QR codes, digital wallets, digital money, etc., in addition to credit cards. Çiçek & Muzaffae (2020) noted that, whereas prior to the pandemic much of e-commerce was in the form of the purchase of travel and accommodation and clothing, the range of products and product groups demanded by consumers during the pandemic increased greatly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tables illustrate the specifics of these categories. Chetana, 2020;China Babu & Kumar, n.d.;Mirchevska et al, 2021;Parlakkiliç et al, 2020;Pham et al, 2020;Riedell, 2021;Salem & Md Nor, 2020;M. H. Sharma & Sharma, 2020) Consumer psychology 5 (Hakim et al, 2021;Kuna, 2020;Namli, 2021;Nugroho et al, 2021;Sihombing & Juliana, 2021) Impulse buying/panic buying 6 (Gazali, 2020;Kaur & Sharma, 2020;Rosita, 2020;Roundha & Pabalkar, 2021;Thakur et al, 2020;Zhang et al, 2020) Product category 16 (Cachero-Martínez, 2020;Chaurasiya et al, 2020;Ćirić et al, 2020;Elshahed & Elsafty, 2021;farradia & Sunarno, 2020;Haskaraca & Bostanci, 2020;Hidayat et al, 2021;Huong & Nguyen, 2021;Lee, 2020;Long & Khoi, 2020;Meshram, 2020;Putri et al, 2021;Rashid et al, n.d.;Sayyida et al, 2021;A.…”
Section: During Covid 19 Literaturementioning
confidence: 99%